Identification of candidate proteins influencing spermatogenesis in Shandong black cattle via integrated multiomics analysis - Qiuyue Zhao; Ruili Liu; Xiuping Miao; Yanfang Mei; Xiuyuan Wang; Jiaxu Ma; Lei Zou; Renzheng Zhang; Xuejin Bai; Yajuan Dong (BMC Genomics)
Abstract Background This study was designed to identify candidate marker proteins that influence the growth and development of Shandong black cattle bull testes through multiomics joint analysis, thereby providing a certain theoretical basis for testis growth and development as well as bull selection. Eight 12-month-old Shandong Black cattle bulls were selected, and testis tissues were collected. The testes were categorized into two groups on the basis of their morphological characteristics: Group 1 (weight > 120 g) and Group 2 (weight < 120 g), with 4 animals in each group. Group 2 was employed as the control group to construct a protein and metabolite library for joint analysis to screen candidate marker proteins that affect testis spermatogenesis. Results The results revealed that 1553 differential expression proteins (DEPs) were differentially expressed between the large and small testes of black Bleykett bulls, with 1219 being upregulated and 334 being downregulated. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment results revealed that the upregulated DEPs were involved primarily in the cell cycle (CDK1, CCNB, MCM4), DNA replication (MCM3, MCM4), etc. The downregulated DEPs were associated mainly with metabolic pathways (ACSM1, IMPDH1), etc. The Gene Ontology (GO) enrichment results revealed that the DEPs were significantly enriched in the categories of cytoskeleton movement. Weighted gene coexpression analysis suggested that testis weight was significantly correlated with MCM, STRADA, and SEC31B. After the DEPs were integrated, a protein–protein interaction (PPI) analysis was performed, and 10 key regulatory proteins, including MCM3, MCM4, CDK1, and CDK2, were identified. Metabolomics demonstrated that 14 upregulated metabolites were predominantly enriched Glycerolipid metabolism (uridine diphosphate glucose), and 59 downregulated metabolites were significantly enriched in metabolic pathways (hypoxanthine). Conclusion A combined analysis revealed that UDPG upregulation enhances MCM3/MCM4 activity during S phase, thereby promoting spermatogenesis. Hypoxanthine upregulation inhibits the activity of CDK1, leading to a blockage in the transition from the G2/M phase of the cell cycle, thereby inhibiting spermatogenesis. In summary, MCM3, MCM4, and CDK1 participate in regulating the process of testis spermatogenesis.